Evaluation of Potential Drug Side Effects in Multidrug-Resistant Tuberculosis Patients who have been Diagnosed by Genexpert Method - Hasanah, Fenny; Dasopang, Eva Sartika; Bakri, Tedy Kurniawan; D, Darmayanto (Asian Journal of Pharmaceutical Research and Development, 2021)
Objective: to evaluation potential drug side effects in multidrug-resistant tuberculosis patients who have been diagnosed by genexpert method Design: this research used a descriptive analysis research design. The population used in this study were MDR-TB patients at the DOTS TB and MDR TB Poly in RSUP Haji Adam Malik Medan in 2017-2019, the research sample obtained was 100 patients and data collection used a cross sectional approach. Interventions: the intervened variable were therapeutic regimen, used of additional drugs and duration of therapy Main outcome measures: the main measurement in this study was therapeutic side effects Results: the results showed that treatment of MDR-TB patients mostly used the standard combination regimen, namely Km-Lfx-Eto-Cs-Z- (H) - (E) as much as 35%. Side effect found was nausea at 20.55%. The use of additional vitamin B6 drugs in MDR-TB patients was 92% because treatment using kanamycin, etionamide, levofloxacin and cycloserine had side effects of peripheral neuropathy. Of the length of treatment that was still undergoing treatment in 2019, the highest number was 59%. Conclusion: it could be concluded the most common side effect found in the average number was nausea at 20.55% and peripheral neuropathy.